Interconnecting Cisco Network Devices, Part 2 (ICND2) Foundation Learning Guide, Fourth Edition - Tiso, John (Cisco Press, 2013)
This Cisco-authorized, self-paced foundation learning tool helps you prepare for both the 200-101 ICND2 and 200-120 CCNA exams. It delivers the higher level of foundational knowledge you need to prepare for the ICND2 exam (and the ICND2 components in the CCNA Composite exam), and to succeed in a wide range of Cisco networking job roles. This book teaches with numerous examples, illustrations, and real-world scenarios, helping you rapidly gain both expertise and confidence. Its coverage ranges from internetworking essentials to advanced diagnostic and debugging techniques that are needed by virtually all Cisco professionals. The book teaches you the technology and theory for building and troubleshooting medium to large scale internetworks, including an in-depth study of VLANs as well as redundancy technologies such as HSRP, STP, and EtherChannel. Additional topics include: implementing scalable mid-sized networks; troubleshooting basic connectivity; implementing EIGRP solutions and OSPF-based scalable multiarea networks; understanding WAN technologies; managing network devices; and advanced troubleshooting. This edition has been fully updated to reflect Cisco's latest exam blueprints. Content has been reorganized, simplified, and expanded to help you learn even more efficiently. The book presents you with information applicable to the CCNA that can't be found in any other CCNA text, including an overview and primer of MPLS, real-world examples, and real-world information on how to more effectively work with the Cisco TAC and diagnose software defects. The book also shows you how to use the Cisco 'Debug' command to learn how protocols work. Interconnecting Cisco Network Devices, Part 2 (ICND2) Foundation Learning Guide, Fourth Edition is part of a recommended learning path from Cisco that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press. To find out more about instructor-led training, e-learning, and hands-on instruction from authorized Cisco Learning Partners worldwide, please visit www.cisco.com/go/authorizedtraining. VLANs, Spanning Tree Protocol (STP), Hot Standby Routing Protocol (HSRP), and EtherChannel Troubleshooting basic connectivity in IPv4, IPv6, and virtualized network environments EIGRP theory, operation, and troubleshooting (IPv4 and IPv6) OSPF terminology, operation, configuration, and troubleshooting (IPv4 and IPv6) WAN technologies, terminology, theory, c ...